Docetic Christology and the Qur’an - Şinasi Gündüz (İslam Tetkikleri Dergisi)
This study address docetic Christology in general and the docetic approach to the main Christian dogmatic belief on the crucifixion of Jesus Christ in particular. It also discusses the claim of Christian writers that an approach among the Muslims is parallel to docetic Christology and criticizes the thesis that the Qur’an exhibits a form of docetic approach. The main argument of the study is that no discussion on Qur’anic verses state that no individual that miraculously resembles Jesus was crucified. Instead, this study intends to elucidate that the claim of the Jews, who supposedly hanged Jesus, was categorically wrong, because this is the only wrong belief based on a presumption. The study also discussed that the slander on Mary and the claim regarding the death of Jesus in Jewish tradition were mainly based on the tradition of Talmud. Moreover, the study highlights a debate that points out that the exegesis of the classical commentaries on the Qur’an regarding the verses in question is mainly related to the Christian and Jewish traditions or the so-called isrâiliyât.